Sympathetic Denervation Accelerates Wound Contraction but Inhibits Reepithelialization and Pericyte Proliferation in Diabetic Mice - Zhifang Zheng; Yu Wan; Yishu Liu; Yu Yang; Jianbing Tang; Wenhua Huang; Biao Cheng (Journal of Diabetes Research)
Previous studies focused on the effects of sympathetic denervation with 6-hydroxydopamine (6-OHDA) on nondiabetic wounds, but the effects of 6-OHDA on diabetic wounds have not been previously reported. In this study, treated mice received intraperitoneal 6-OHDA, and control mice received intraperitoneal injections of normal saline. Full-thickness wounds were established on the backs of mice. The wounds were sectioned (four mice per group) for analysis at 2, 5, 7, 10, 14, 17, and 21 days after injury. The wound areas in the control group were larger than those in the treatment group. Histological scores for epidermal and dermal regeneration were reduced in the 6-OHDA-treated group on day 21. The mast cells (MCs) in each field decreased after sympathectomy on days 17 and 21. The expression levels of norepinephrine, epidermal growth factor (EGF), interleukin-1 beta, NG2 proteoglycan, and desmin in the treatment group were less than those in the control group. In conclusion, 6-OHDA delays reepithelialization during wound healing in diabetic mice by decreasing EGF, but increases wound contraction by reducing IL-1β levels and the number of MCs. Besides, 6-OHDA led to reduced pericyte proliferation in diabetic wounds, which might explain the vascular dysfunction after sympathetic nerve loss in diabetic wounds.